A safety coating and its application, electrode sheet and lithium ion battery

By using safety coatings with a particle size limited inorganic filler and an optimized binder ratio in a specific range in the lithium battery cell, the problem of insufficient battery cell performance in the prior art is solved, and higher safety and performance are achieved.

CN118970023BActive Publication Date: 2025-03-07ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411453782.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-07
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing safety coatings cannot effectively improve the rate performance, low temperature performance and cycling performance of lithium battery cells, and there are problems of increasing the internal resistance and polarization of the battery cells.

Method used

Using a safety coating containing an inorganic filler and a first binder, the safety performance and performance of the battery cell are improved by limiting the particle size of the inorganic filler and optimizing the binder. Specific measures include: the inhomogeneity coefficient Cu and curvature coefficient Cc of the inorganic filler are between 2≤Cu≤18 and 0.5≤Cc≤3.1, the mass fraction w of the binder satisfies w=k×(Cu)0.5/Dv50, and 0.2≤k≤2.

Benefits of technology

It improves the safety performance of the battery cell, improves the rate performance, low-temperature discharge performance and cycling performance, reduces the probability of short circuit of the positive and negative electrodes, and improves the overall performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118970023B_ABST
    Figure CN118970023B_ABST
Patent Text Reader

Abstract

The present invention discloses a safety coating and its application, an electrode sheet and a lithium-ion battery, and relates to the technical field of secondary battery materials. By limiting the particle size of inorganic fillers in the safety coating, the grading of large and small particles is achieved, which can make the safety coating have a denser structure, thereby reducing the probability of contact between the positive and negative electrodes, thereby improving the safety performance of the battery core. At the same time, the amount of binder in the safety coating is optimized to promote the absorption of electrolyte by the safety coating, which can improve the rate performance, low-temperature discharge performance and cycle performance of the battery core. Finally, the present invention can improve the rate performance, low-temperature discharge performance and cycle performance of the battery core while improving the safety performance of the battery core by limiting the particle size of inorganic fillers and selecting binders.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery materials, and in particular to a safety coating and application thereof, an electrode sheet and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in products such as 3C, electric vehicles and power tools due to their advantages such as high energy density, no memory effect, long cycle life, environmental friendliness and ability to adapt to various environments.

[0003] In practical applications, the requirements for the safety and cycle performance of lithium batteries are becoming increasingly higher. In order to improve the safety performance of batteries, the introduction of safety coatings in the pole pieces of batteries is one of the commonly used measures in the industry. Most safety coatings contain a certain proportion of inorganic fillers, conductive agents and binders. However, the structure of conventional safety coatings is relatively loose, which cannot effectively improve the safety performance of the battery cell, and will increase the internal resistance of the battery cell, resulting in increased polarization of the battery cell, and deterioration of low temperature performance, rate performance and cycle performance. Lithium-ion batteries are subject to kinetic limitations and are prone to lithium precipitation, resulting in reduced cycle performance and rate performance of the battery cell. When lithium precipitation occurs, the increase in side reactions will lead to the consumption of electrolyte. At the same time, the formation of new solid electrolyte interface film (SEI) during the cycle process will also cause further consumption of electrolyte, accelerating the deterioration of cycle performance. In addition, when the battery cell is subjected to mechanical abuse tests such as needle puncture, the positive and negative electrodes of the battery may also short-circuit and thermal runaway, leading to test failure.

[0004] Therefore, it is of great significance to solve the problem that current safety coatings cannot effectively improve the rate performance and cycle performance of battery cells, and to provide a safety coating that can improve the rate performance, low-temperature discharge performance and cycle performance of battery cells while improving the safety performance of battery cells. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a safety coating and its application, an electrode sheet and a lithium-ion battery, aiming to solve the problem that the current safety coating cannot effectively improve the low temperature performance, rate performance and cycle performance of the battery cell.

[0006] In a first aspect of the present invention, a safety coating for an electrode sheet in a secondary battery is provided. The raw materials of the safety coating include an inorganic filler and a first binder. The non-uniformity coefficient C of the inorganic filler is u Satisfy 2≤C u ≤18, curvature coefficient C c Satisfy 0.5≤C c ≤3.1; the mass fraction w of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / Dv50 , and 0.2≤k≤2, k is a constant, and the mass fraction w of the first binder in the safety coating ranges from 1% to 21.2%;

[0007] Among them, the non-uniformity coefficient C u The calculation formula is: C u =D v90 / D v10 , the curvature coefficient C c The calculation formula is: C c =D v50 ×D v50 / (D v10 ×D v90 );

[0008] D v10 , D v50 , D v90 They are the particle sizes corresponding to the cumulative values ​​of the volume distribution of the inorganic filler reaching 10%, 50% and 90% respectively.

[0009] The safety coating according to the embodiment of the present invention has at least the following beneficial effects: the safety coating provided by the present invention comprises an inorganic filler and a binder, and by limiting the particle size of the inorganic filler and selecting the binder, the rate performance, low temperature discharge performance and cycle performance of the battery cell can be improved while improving the safety performance of the battery cell. v10 , D v50 , D v90 Should satisfy 2≤Cu=D v90 / D v10 ≤18,0.5≤C c =D v50 ×D v50 / (D v10 ×D v90 )≤3.1,C u and C c are the uniformity coefficient and curvature coefficient of the inorganic filler, D v10 , D v50 , D v90 are the particle sizes corresponding to the cumulative values ​​of the volume distribution of the inorganic filler reaching 10%, 50% and 90% respectively. When the particle size of the inorganic filler satisfies the above relationship, the continuity of its gradation curve is good, and the gradation of fine particles and coarse particles is good, which can make the safety coating have a denser structure, thereby reducing the probability of short circuit between the positive and negative electrodes and improving the safety performance of the battery cell. The mass fraction w of the first binder should satisfy w=k×(C u ) 0.5 / D v50, 0.2≤k≤2, when k is within the above range, the binder not only has sufficient bonding force and small polarization of the battery cell, but also can promote the safety coating to absorb the electrolyte, improve the rate performance, low-temperature discharge performance and cycle performance of the battery cell. Finally, the safety coating provided by the present invention, by limiting the particle size of the inorganic filler, realizes the grading of large and small particles, can make the safety coating have a denser structure, thereby reducing the probability of contact between the positive and negative electrodes, thereby improving the safety performance of the battery cell. At the same time, the amount of binder in the safety coating is optimized to promote the safety coating to absorb the electrolyte, which can improve the rate performance, low-temperature discharge performance and cycle performance of the battery cell.

[0010] In the present invention, the non-uniformity coefficient C of the inorganic filler particle size is u =D v90 / D v10 Should satisfy: 2≤C u =D v90 / D v10 ≤18. Unevenness coefficient (C u ) is an important parameter to describe the particle size distribution of inorganic fillers, which reflects the unevenness of the particle size of inorganic fillers. u When C is greater than 18, it indicates that the distribution range of the inorganic filler particle size is relatively wide, and some particles with particularly large particle sizes may be missed during the coating of the safety coating, thus adversely affecting the safety performance of the battery cell. u When the ratio is less than 2, the distribution range of the particle size of the inorganic filler particles is narrow, the particle size of most particles is similar, there are not enough fine particles to fill the gaps between large particles, and there is a poor gradation phenomenon. At this time, the density of the safety coating is low, which has an adverse effect on the safety performance and energy density of the battery. When it is within the above range, the safety coating can have a denser structure, and it is not easy to leak when applying the safety coating, and the overall performance is better.

[0011] In the present invention, the curvature coefficient C of the inorganic filler is c =D v50 ×D v50 / (D v10 ×D v90 ) should satisfy: 0.5≤C c =D v50 ×D v50 / (D v10 ×D v90 )≤3.1. Curvature coefficient (C c ) is a parameter that describes the shape of the particle size distribution curve. c When the value of is 1, the particle size distribution of the inorganic filler is in an ideal state, the particle size distribution is continuous, there is no obvious particle size jump or loss, and the shape of the particle size distribution curve is uniform, that is, the transition from fine particles to coarse particles is smooth.c When C is not equal to 1, it indicates that the distribution of inorganic filler particle size deviates from the ideal state. c When C is greater than 1, it means that the particle size distribution curve is convex on the logarithmic particle size graph, that is, the particle size distribution of the fine particle part is more concentrated than that of the coarse particle part. c When it is less than 1, it means that the particle size distribution curve is concave, that is, the particle size distribution of the coarse particle part is more concentrated than that of the fine particle part. However, the distribution of the particle size of the inorganic filler often deviates from the ideal state. Most of the inorganic fillers are fine particles or coarse particles. The overall shape of the gradation curve is discontinuous, resulting in a high porosity and a low density of the safety coating. c The value range of is limited to the above values, which can ensure the continuity of the grading curve, thus facilitating the improvement of the density of the safety coating.

[0012] In the present invention, the amount w of the first binder should satisfy w=k×(C u ) 0.5 / D v50 , 0.2≤k≤2, where k is a constant related to the density of the inorganic filler. Generally speaking, when the particle shape and pore structure are determined, the D v50 The smaller it is, the larger its specific surface area is, and the larger the contact area with the binder is. Accordingly, the amount of binder needs to be increased. u It shows the distribution of particles, C u Smaller values ​​mean that all particle sizes tend to be closer to D v50 , the number of fine particles in the system is small, which will make the overall specific surface area smaller, thereby reducing the amount of binder used. The k value indicates the level of binder used in the safety coating. When k is less than 0.2, the adhesion between the safety coating and the current collector is poor, and there is a risk of falling off; when k is greater than 2, it will lead to an increase in the polarization of the battery cell, resulting in a deterioration in the rate performance, low-temperature discharge performance and cycle performance of the battery cell. When the range of k is 0.2~2, not only is the adhesion sufficient, the polarization of the battery cell is small, but it can also promote the absorption of the electrolyte by the safety coating, and improve the rate performance, low-temperature discharge performance and cycle performance of the battery cell.

[0013] In some embodiments of the present invention, the median particle size D of the inorganic filler is v50 The range is 0.2~4μm, and the specific surface area is 5~50m 2 / g. When the inorganic filler D v50 Less than 0.2 μm, and the specific surface area is greater than 50 m 2 / g, the inorganic filler is prone to agglomeration and difficult to disperse; when the inorganic filler D v50 Greater than 4 μm, and specific surface area less than 5 m 2 / g, it is difficult to obtain a thin safety coating due to the large particle size, which affects the energy density of the battery cell, and the primer is easily missed when the safety coating is applied, affecting the safety of the battery cell. When the median particle size and specific surface area of ​​the inorganic filler are between the above ranges, a better balance can be achieved between the processability of the safety coating and the energy density of the battery cell.

[0014] In some embodiments of the present invention, the inorganic filler includes one or more of aluminum oxide, boehmite, aluminum hydroxide, magnesium hydroxide, silicon dioxide, titanium dioxide, lithium iron phosphate, lithium iron manganese phosphate, lithium aluminum titanium phosphate, lithium lanthanum titanate or lithium lanthanum zirconium oxide, preferably boehmite. The inorganic filler used in the present invention can be an inert inorganic filler such as aluminum oxide, boehmite, aluminum hydroxide, magnesium hydroxide, silicon dioxide and titanium dioxide, or an active material such as lithium iron phosphate and lithium iron manganese phosphate that can exert a certain capacity and good thermal stability, or a solid electrolyte such as lithium aluminum titanium phosphate (LATP), lithium lanthanum titanate (LLTO) and lithium lanthanum zirconium oxide (LLZO). Boehmite is preferably used. Compared with other inorganic fillers, boehmite is not only cheap, but also has a lower Rockwell hardness and less wear on the gravure roller, thereby reducing manufacturing costs.

[0015] In some embodiments of the present invention, the mass fraction of the inorganic filler in the safety coating is 73.8% to 98.5%.

[0016] In some embodiments of the present invention, the first binder includes one or more of a polyvinylidene fluoride (PVDF) binder, a sodium carboxymethyl cellulose (CMC) binder, or a polyacrylate (PAA) binder.

[0017] In some embodiments of the present invention, the mass fraction of the first binder in the safety coating is 1wt%~21.2wt%, preferably 5wt%~15wt%. When the amount of binder in the safety coating is less than 1%, the safety coating has insufficient adhesion and is prone to fall off during later use; when the amount of binder is greater than 21.2%, the safety coating will be difficult to process during gravure printing, and the internal resistance of the battery cell will also be deteriorated. In addition, the amount of binder is 1%~21.2%, and the pH of the slurry can be adjusted to below 8.5, thereby reducing the corrosion of the alkaline active substance aqueous solution to the current collector aluminum foil.

[0018] In some preferred embodiments of the present invention, the first adhesive is a polyacrylate adhesive, which can reduce the corrosion of the active substance to the aluminum foil, has good bonding performance, is cheap, and the solvent is deionized water, which is environmentally friendly.

[0019] In some embodiments of the present invention, the structural formula of the polyacrylate binder is:

[0020] ;

[0021] Among them, R 1 Each occurrence is independently selected from H, Li or Na;

[0022] R 2 Each occurrence is independently selected from substituted or unsubstituted C 1 ~C 10 The alkyl group;

[0023] And 5≤(x+z) / y≤20, 1.2≤z / x≤2, x, y, z are all not 0.

[0024] The polyacrylate adhesive provided by the present invention is obtained by modifying the cyano group (-CN) and ester group (-COOR 2 ) and carboxylates (-COOR 1 ) content is limited, so as to achieve good bonding performance; and the binder is water-soluble, the solvent is water, no harmful organic solvents such as NMP are needed, it is harmless to the human body and environmentally friendly; it is abundant in source, cheap, and can be widely used in industrial production. The above-mentioned binder is introduced into the electrode sheet as the raw material of the water-based safety coating. Based on its excellent bonding performance, the water-based safety coating can be firmly adhered to the collector surface of the electrode sheet, which can not only reduce the surface contact resistance, but also reduce the generation of collector burrs during safety testing of the battery cell, and reduce the contact short circuit between the collector burrs and the active substances in the unstable charging state, thereby improving the safety of the battery cell. In addition, by limiting the molecular weight of the binder and the content of cyano, ester and carboxylate groups in the molecular chain, the absorption rate of the binder electrolyte can be adjusted, which can significantly improve the rate performance and high and low temperature discharge performance of the battery cell, and improve the safety performance and cycle performance of the battery.

[0025] The binder provided by the present invention has a molecular chain containing a cyano group (-CN, the number of which accounts for n 1 , n 1 =z / (x+y+z))、carboxylate(-COOR 1 , R 1 Each occurrence is independently selected from H, Li, and Na, and its number accounts for n in all side chain groups 2 , n 2 =x / (x+y+z)) and ester groups (-COOR 2 , R 2 Each occurrence is independently selected from substituted or unsubstituted C 1 ~C 10 The number of alkyl groups in all side chain groups accounts for n 3 , n 3 =y / (x+y+z)), n1 +n 2 +n 3 =1.

[0026] Among them, -CN is a strongly polar group with good electrolyte affinity and electrochemical stability, and can provide greater adhesion. However, this group is very rigid and cannot cope with the huge volume changes that occur when lithium ions are embedded in / out of the active material.

[0027] Among them, -COOR 1 They carry negative charges and repel each other, which helps the stretching of the binder molecules and promotes the uniform dispersion of the conductive agent. At the same time, they can also regulate the swelling degree of the binder in the electrolyte solvent, reduce the erosion of the adhesive by the electrolyte dissolution, and better maintain the bonding ability and bonding effect.

[0028] Among them, -COOR 2 The polarity and solubility parameters are close to those of carbonate solvents in the electrolyte, which is conducive to the binder's moderate absorption of the electrolyte. The absorption of the electrolyte will plasticize the binder, making it elastic and flexible to adapt to the periodic volume changes of the electrode active material during the charging and discharging process as lithium ions are inserted and extracted. At the same time, the absorption of the electrolyte will also increase the ionic conductivity of the water-based safety coating and promote the improvement of the low-temperature discharge performance of the battery cell.

[0029] Binders are an essential part for maintaining the integrity of the electrode, and are very important for improving the battery's specific capacity, cycle stability and other performance. Polyacrylic acid is used as a binder for the positive and negative electrodes of lithium batteries because it contains more polar functional groups, is soluble in water and has good adhesion. However, the polar groups of polyacrylic acid cause the hydrogen bonds formed between the molecular chains to result in a large chain rigidity, which is not conducive to maintaining the integrity of the electrode during the charge and discharge process. Therefore, it is imperative to control the number of polyacrylic acid functional groups, change the type of functional groups and the structure of the polyacrylic acid molecular chain in order to improve the electrical performance of lithium batteries. The present invention limits the content of cyano, ester and carboxylate groups in the binder molecular chain: (1) 1.2≤z / x≤2, that is, n 1 、n 2 Satisfy 1.2≤n 1 / n 2 ≤2; when n 1 / n 2 <1.2, it is easy to cause insufficient bonding strength of the adhesive; and when n 1 / n 2 >2, the molecular chain is in a curled state, which is not conducive to the dispersion of the conductive agent, and the binder is more susceptible to the swelling of the electrolyte; (2) 5≤(x+z) / y≤20, that is, n 1 、n 2 、n 3 Satisfy 5≤(n 1 +n 2) / n 3 ≤20; when (n 1 +n 2 ) / n 3 When <5, the binder contains excessive -COOR 2 At this time, the binder easily absorbs excess electrolyte, the bonding force decreases rapidly, the elasticity deteriorates, and the performance of the battery cell deteriorates; when (n 1 +n 2 ) / n 3 >20, -COOR in the binder 2 If the content is too low, the elasticity of the binder is insufficient, the ionic conductivity of the water-based safety coating is low, and the low-temperature discharge performance and rate discharge performance of the battery cell are significantly reduced. Finally, the present invention achieves good bonding strength of the binder by regulating the content of cyano, ester and carboxylate groups in the binder molecular chain, and adjusts the electrolyte absorption rate of the binder, thereby improving the rate and high and low temperature discharge performance of the battery cell.

[0030] In some embodiments of the present invention, R 2 Each occurrence is independently selected from C 1 ~C 10 A straight chain alkyl, branched chain alkyl or cycloalkyl group, preferably C 1 ~C 10 A straight chain alkyl group, more preferably C 1 ~C 4 of alkyl.

[0031] In some embodiments of the present invention, the electrolyte absorption rate c of the polyacrylate binder at 80° C. is 10% to 50%, for example, 10% to 20%, 20% to 30%, 30% to 40%, or 40% to 50%.

[0032] The present invention achieves the adjustment of the electrolyte absorption rate of the binder by limiting the content of cyano, ester and carboxylate groups in the binder molecular chain. The electrolyte absorption rate c of the binder at 80°C satisfies 10%≤c≤50%. When c<10%, the binder absorbs insufficient electrolyte, has poor elasticity, and cannot buffer the periodic volume changes caused by the insertion and extraction of lithium ions from the active material. In addition, the ionic conductivity of the water-based safety coating is low, and the low-temperature discharge performance and rate discharge performance of the battery cell deteriorate. When c>50%, the binder absorbs excessive electrolyte, the water-based safety coating expands, the bonding force decreases, and the internal resistance increases, which also leads to the deterioration of the battery cell performance.

[0033] In some embodiments of the present invention, the weight average molecular weight M of the polyacrylate binder is wThe range is 200000~500000, for example, it can be 200000, 250000, 300000, 350000, 400000, 450000, and 500000.

[0034] In some embodiments of the present invention, the number average molecular weight M of the polyacrylate binder is n The range is 100000~400000, for example, it can be 100000, 150000, 200000, 250000, 300000, 350000, and 400000.

[0035] In some embodiments of the present invention, the weight average molecular weight M of the polyacrylate binder is w and number average molecular weight M n The ratio satisfies M w / M n ≤3, preferably M w / M n The range is 1.5~1.9.

[0036] If the molecular weight of the binder is too low, not only will the bonding force be too low, but it will also lead to an increase in the amount of binder used; if the molecular weight is too high, the viscosity will be too high and processing will be difficult. w / M n >3. The molecular weight distribution of the binder is too dispersed, which deteriorates the performance of the water-based safety coating.

[0037] In some embodiments of the present invention, the mass fraction of the polyacrylate binder in the safety coating is 1wt%~21.2wt%, preferably 5wt%~15wt%. When the amount of binder in the safety coating is less than 1%, the safety coating has insufficient adhesion and is prone to fall off during later use; when the amount of binder is greater than 21.2%, the safety coating will be difficult to process during gravure printing, and the internal resistance of the battery cell will also be deteriorated. In addition, the amount of binder is 1%~21.2%, and the pH of the slurry can be adjusted to below 8.5, thereby reducing the corrosion of the alkaline active substance aqueous solution to the current collector aluminum foil.

[0038] The polyacrylate binder can be prepared by conventional preparation methods in the art, for example, by any one of emulsion polymerization, solution polymerization, bulk polymerization and suspension polymerization.

[0039] In a specific embodiment, the present invention also provides a method for preparing the above-mentioned polyacrylate adhesive, comprising the steps of:

[0040] S1, adding a dispersion medium into a reaction vessel and deoxygenating;

[0041] S2, according to the ratio of x, y, z, add a certain amount of acrylonitrile to the reaction vessel to provide -COOR 1 Monomer A, providing -COOR 2 Monomer B;

[0042] S3, adding initiator and heating to initiate reaction;

[0043] S4. After the reaction is completed, the product is filtered, dried, crushed and sieved to obtain a polyacrylate adhesive.

[0044] In some embodiments of the present invention, the monomer A includes at least one of acrylic acid, lithium acrylate, and sodium acrylate, but is not limited thereto. The purpose of adding monomer A is to provide -COOR 1 , R 1 Selected from H, Li or Na, those skilled in the art can independently select a suitable monomer A according to their needs, which should be regarded as a reasonable change within the scope of the present invention.

[0045] In some embodiments of the present invention, the monomer B includes at least one of methyl acrylate, ethyl acrylate, and butyl acrylate, but is not limited thereto. 1 ~C 10 The purpose of adding monomer B is to provide -COOR 2 , R 2 Selected from substituted or unsubstituted C 1 ~C 10 Those skilled in the art can select suitable monomer B according to their needs, which should be regarded as reasonable changes within the scope of the present invention.

[0046] In some embodiments of the present invention, in step S1, distilled water is added to the reaction container, stirring is started, and high-purity nitrogen is introduced for deoxygenation.

[0047] In some embodiments of the present invention, in step S2, acrylonitrile is added to provide -COOR 1 Monomer A, providing -COOR 2 After adding monomer B, heat to 65°C under an inert atmosphere and keep the temperature constant.

[0048] In some embodiments of the present invention, the initiator includes 20% ammonium persulfate, but is not limited thereto.

[0049] In some embodiments of the present invention, the raw material of the safety coating further includes a first conductive agent. The safety coating satisfies at least one of the following:

[0050] A1) The mass fraction of the first conductive agent in the safety coating is 0.5% to 5%;

[0051] A2) The mass ratio of the first conductive agent, the first binder, and the inorganic filler is (0.5-5): (1-21.2): (73.8-98.5);

[0052] A3) The raw materials of the safety coating also include heat-stable active substances;

[0053] A4) When A3) is included, the mass ratio of the first conductive agent, the first binder, the inorganic filler, and the thermally stable active material is (0.5-5): (1-21.2): (1-97.5): (1-97.5);

[0054] A5) When A3) is included, the thermally stable active material includes one or both of lithium iron phosphate and lithium manganese iron phosphate.

[0055] In some embodiments of the present invention, the mass fraction of the first conductive agent in the safety coating is 0.5% to 5%. Preferably, it is 1% to 3.5%. If the conductive agent content is too low, the water-based safety coating film resistance will be too large and the battery cell cycle performance will be poor; if the content is too high, the water-based safety coating film resistance will be too low and the battery cell safety will be poor. When the content of the conductive agent is between 0.5wt% and 5wt%, both safety and cycle can be taken into account.

[0056] In some embodiments of the present invention, the first conductive agent includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers, and conductive carbon black. The present invention has no special requirements for the first conductive agent, and any conventional conductive agent in the art can be used, such as conductive carbon black or carbon nanotubes, and more specifically, super dense high conductive carbon black SUPER P Li.

[0057] In some embodiments of the present invention, the mass ratio of the first conductive agent, the first binder, and the inorganic filler is (0.5-5): (1-21.2): (73.8-98.5). For example, in terms of weight, the first conductive agent can be 0.5-5 parts, preferably 1.5-3 parts, the first binder can be 1-21.2 parts, preferably 5-15 parts, and the inorganic filler can be 73.8-98.5 parts.

[0058] In some embodiments of the present invention, the raw materials of the safety coating further include a thermally stable active substance.

[0059] In some embodiments of the present invention, the mass ratio of the first conductive agent, the first binder, the inorganic filler, and the thermally stable active material is (0.5-5): (1-21.2): (1-97.5): (1-97.5).

[0060] In some embodiments of the present invention, the raw materials of the safety coating include a first binder, a first conductive agent, an inorganic filler, and a thermally stable active substance, and the mass ratio thereof satisfies: first conductive agent: first binder: inorganic filler: thermally stable active substance = (0.5-5): (1-21.2): (1-97.5): (1-97.5). For example, in terms of weight, the first conductive agent may be 0.5-5 parts, the first binder may be 1-21.2 parts, the inorganic filler may be 1-97.5 parts, and the thermally stable active substance may be 1-97.5 parts.

[0061] In some embodiments of the present invention, the thermally stable active material includes one or both of lithium iron phosphate and lithium manganese iron phosphate.

[0062] In a second aspect of the present invention, an electrode sheet is provided, comprising: a current collector, an active material layer and the above-mentioned safety coating.

[0063] The electrode sheet according to the embodiment of the present invention has at least the following beneficial effects: The present invention provides an electrode sheet comprising a safety coating. The safety coating comprises a binder and the above-mentioned inorganic filler and conductive agent. By limiting the particle size of the inorganic filler and selecting the binder content, the rate performance, low-temperature discharge performance and cycle performance of the battery cell can be improved while improving the safety performance of the battery cell. Introducing the above-mentioned safety coating into the electrode sheet can not only improve the safety performance of the battery, but also significantly improve its rate performance, low-temperature discharge performance and cycle performance.

[0064] In some embodiments of the present invention, the safety coating is coated on at least one side surface of the current collector, and the active material layer is coated on the side surface of the safety coating away from the current collector and / or on the side surface of the current collector away from the aqueous safety coating.

[0065] Specifically, the electrode sheet is a positive electrode sheet, the safety coating is coated on at least one side of the current collector, and the active material layer is coated on the side of the safety coating away from the current collector and / or on the side of the current collector away from the aqueous safety coating.

[0066] More specifically, the electrode sheet is a positive electrode sheet, the safety coating is coated on both side surfaces of the current collector, and the active material layer is coated on the surface of the safety coating away from the current collector.

[0067] In other embodiments of the present invention, the active material layer is coated on at least one side surface of the current collector, and the safety coating is coated on the side surface of the active material layer away from the current collector and / or on the side surface of the current collector away from the active material layer.

[0068] Specifically, the electrode sheet is a negative electrode sheet, the active material layer is coated on at least one side of the current collector, and the safety coating is coated on the side of the active material layer away from the current collector and / or on the side of the current collector away from the active material layer.

[0069] More specifically, the electrode sheet is a negative electrode sheet, the active material layer is coated on both side surfaces of the current collector, and the safety coating is coated on the surface of the active material layer away from the current collector.

[0070] The electrode sheet provided by the present invention can be used as a positive electrode sheet or a negative electrode sheet, preferably a positive electrode sheet. When used as a positive electrode sheet, the safety coating is closer to the current collector, and its structure is "current collector-safety coating-active material layer", such as Figure 1 As shown, the positive electrode sheet 01 includes the following structures: a current collector 022; a safety coating 023, which is disposed on at least one surface of the current collector 022; and an active material layer 011, which is disposed on the surface of the safety coating 023 away from the current collector 022. When used as a negative electrode sheet, the active material layer is closer to the current collector, and its structure is "current collector-active material layer-safety coating".

[0071] The internal short circuit of lithium-ion batteries can generally be divided into several types: 1) short circuit between positive and negative current collectors; 2) short circuit between positive and negative active materials; 3) short circuit between negative active material and positive current collector; 4) short circuit between positive active material and negative current collector. Among them, the impedance of the short circuit point between the negative active material and the positive current collector is small, and the trigger temperature of the negative exothermic reaction is low. Therefore, the short circuit between the negative active material and the Al foil is the most dangerous. The present invention introduces a safety coating with high adhesion to the surface of the positive current collector to reduce the probability of contact between the positive current collector and the negative active material, which can effectively improve the safety performance of the battery cell.

[0072] In some embodiments of the present invention, the thickness of the safety coating is 1-20 μm, for example, 1-7 μm, 7-14 μm, or 14-20 μm.

[0073] In some embodiments of the present invention, the coating surface density of the safety coating is 2-35 mg / 1540.25 mm 2 . For example, it can be 2~8 mg / 1540.25mm 2 , 8~15 mg / 1540.25mm 2 , 14~21 mg / 1540.25mm 2 , 20~28 mg / 1540.25mm 2 , 28~35 mg / 1540.25mm 2 .

[0074] There is a positive correlation between the coating surface density of the safety coating and its thickness. If the thickness is too low, the safety performance of the battery cell will be poor; if the thickness is too large, the energy density of the battery cell will be reduced.

[0075] In some embodiments of the present invention, the membrane resistance of the safety coating at a pressure of 0.4 t is 0.5~5Ω, for example, 0.5~2Ω, 2~3.5Ω, 3.5~5Ω. The membrane resistance of the safety coating is the primary factor affecting the safety performance of the battery cell. If the value is too small, the safety performance of the battery cell will deteriorate, and if it is too large, the cycle performance of the battery cell will deteriorate. The value is between 0.5~5Ω@0.4T, which can take into account both safety performance and cycle performance.

[0076] In some embodiments of the present invention, the bonding force between the safety coating and the current collector is not less than 100 N / m. If the bonding force is less than 100 N / m, there is a risk that the water-based safety coating will fall off during subsequent use.

[0077] In some embodiments of the present invention, the raw materials of the active material layer include active material, a second conductive agent and a second binder.

[0078] In some embodiments of the present invention, the mass percentage of the active material in the active material layer is 90% to 98%.

[0079] In some embodiments of the present invention, the mass percentage of the second conductive agent in the active material layer is 0.5% to 5%, preferably 0.5% to 2%. If the content of the second conductive agent is too low, the battery cell cycle performance is poor; if the content is too high, it is good for improving the cycle performance, but will lead to poor safety performance of the battery cell.

[0080] In some embodiments of the present invention, the second conductive agent includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers, and conductive carbon black. The present invention has no special requirements for the second conductive agent, and any conventional conductive agent in the art can be used, such as conductive carbon black or carbon nanotubes, and more specifically, super dense high conductive carbon black SUPER P Li.

[0081] In some embodiments of the present invention, the mass percentage of the second binder in the active material layer is 0.5% to 5%. If the amount of the second binder is too little, the active material layer will not have sufficient bonding strength and will easily fall off during later use; if the amount of the second binder is too much, the active material layer will be difficult to process and the internal resistance of the battery cell will also be deteriorated.

[0082] In some embodiments of the present invention, the second binder includes at least one of polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC, styrene butadiene rubber SBR, and PAA-based binders. The present invention has no special requirements for the second binder, and any conventional binder in the art can be used.

[0083] In a specific embodiment, the active material layer may be a positive electrode active material layer, and the raw materials of the positive electrode active material layer include a positive electrode active material, a second conductive agent, and a second binder.

[0084] The positive electrode active material is not limited, and can be one or more of common lithium cobalt oxide, lithium iron phosphate and ternary materials, and the amount used is 90wt% to 98wt% of the total weight of the active material layer. Under the condition of ensuring that the active material has a certain conductivity and adhesion, the higher the content of the active material, the better, so that the battery cell has a higher energy density.

[0085] The second binder is not limited and can be a common cathode binder, including polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC and PAA binders, and the amount used is 0.5wt%~5wt% of the total weight of the active material layer. If the amount of the second binder is too little, the active material layer will not have enough adhesion and will easily fall off during later use; if the amount of the second binder is too much, the active material layer will be difficult to process and the internal resistance of the battery will also be deteriorated. Considering that it does not directly contact the current collector, the upper limit of its amount can be appropriately reduced to ensure that the positive active material does not fall off during the use of the battery. At the same time, a lower amount can also improve the cycle performance of the battery, increase the amount of positive active material, and improve the energy density of the battery.

[0086] In a specific embodiment, the active material layer may be a negative electrode active material layer, and the raw materials of the negative electrode active material layer include a negative electrode active material, a second conductive agent, and a second binder.

[0087] The negative electrode active material is not limited and can be one or more of common artificial graphite, natural graphite, modified graphite, silicon oxide compounds, silicon carbon composites and other silicon negative electrode materials, and the amount used is 90wt%~98wt% of the total weight of the active material layer.

[0088] In some embodiments of the present invention, the electrode sheet further includes a current collector. The current collector is not limited and can be a common current collector. For example, when the electrode sheet is a positive electrode sheet, the current collector can be an aluminum foil or a composite aluminum foil; when the electrode sheet is a negative electrode sheet, the current collector can be a copper foil or a composite copper foil.

[0089] In some preferred embodiments of the present invention, the dyne value of the current collector is ≥30 dyn / cm, preferably ≥38 dyn / cm.

[0090] In some embodiments of the present invention, the safety coating is coated on both side surfaces of the current collector.

[0091] The safety coating satisfies at least one of the following requirements:

[0092] B1) the double-sided thickness of the safety coating is 1-20 μm;

[0093] B2) The double-sided coating density of the safety coating is 2-35 mg / 1540.25 mm 2 ;

[0094] B3) The double-sided membrane resistance of the safety coating tested under a pressure of 0.4 t is 0.5~5Ω;

[0095] B4) The double-sided thickness d of the safety coating and the value of the double-sided diaphragm resistance R under a pressure of 0.4 t satisfy the condition: 2≤R×d≤50;

[0096] B5) The distance W between the left edge of the safety coating on the A side of the current collector and the left edge of the current collector along the direction perpendicular to the unwinding direction of the current collector A1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is A2 The range is 3mm~30mm; the distance W between the left edge of the safety coating on the B side of the current collector and the left edge of the current collector B1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is B2 The range is 3mm~30mm; and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm.

[0097] In some embodiments of the present invention, the double-sided thickness d of the safety coating (ie, the sum of the thicknesses of the safety coatings coated on both sides of the current collector surface) is 1-20 μm, for example, 1-7 μm, 7-14 μm, or 14-20 μm.

[0098] In some embodiments of the present invention, the double-sided coating density of the safety coating (i.e., the sum of the coating density of the safety coatings coated on both sides of the current collector surface) is 2-35 mg / 1540.25 mm 2 . For example, it can be 2~8mg / 1540.25mm 2 ,8~15mg / 1540.25mm 2 , 14~21mg / 1540.25mm 2 20~28mg / 1540.25mm2 , 28~35mg / 1540.25mm 2 .

[0099] There is a positive correlation between the coating surface density of the safety coating and its thickness. If the thickness is too low, the safety performance of the battery cell will be poor; if the thickness is too large, the energy density of the battery cell will be reduced.

[0100] In some embodiments of the present invention, the double-sided membrane resistance R of the safety coating under a pressure of 0.4 t (i.e., the sum of the membrane resistances of the safety coating on both sides coated on the surface of the current collector) is 0.5~5Ω, for example, 0.5~2Ω, 2~3.5Ω, 3.5~5Ω. The membrane resistance of the safety coating is the primary factor affecting the safety performance of the battery cell. If the value is too small, the safety performance of the battery cell will deteriorate, and if it is too large, the cycle performance of the battery cell will deteriorate. The value is between 0.5~5Ω@0.4T, which can take into account both safety performance and cycle performance.

[0101] In some embodiments of the present invention, the double-sided thickness d (in μm) of the safety coating and the double-sided membrane resistance R (in Ω) under a pressure of 0.4t satisfy the condition: 2≤R×d≤50. Generally speaking, the parameters R and d are positively correlated with the safety of the battery cell, and negatively correlated with the cycle performance of the battery cell. When the relationship 2≤R×d≤50 is satisfied, a good balance can be achieved between the safety performance and electrochemical performance of the battery cell.

[0102] In some embodiments of the present invention, the bonding force between the safety coating and the current collector is not less than 100 N / m. If the bonding force is less than 100 N / m, there is a risk that the safety coating will fall off during subsequent use.

[0103] In a specific embodiment, the present invention provides a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material layer, a safety coating and a positive electrode current collector. The raw materials of the safety coating include an inorganic filler and a first binder; the non-uniformity coefficient C of the inorganic filler is u Satisfy 2≤C u ≤18, curvature coefficient C c Satisfy 0.5≤C c ≤3.1; the mass fraction w of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , and 0.2≤k≤2; wherein the non-uniformity coefficient C u The calculation formula is: C u =D v90 / D v10 , the curvature coefficient C c The calculation formula is: C c =Dv50 ×D v50 / (D v10 ×D v90 );D v10 , D v50 , D v90 are the particle sizes corresponding to the cumulative values ​​of the volume distribution of the inorganic filler reaching 10%, 50% and 90% respectively; k is a constant related to the density of the inorganic filler.

[0104] The positive electrode provided by the present invention introduces a safety coating, which contains an inorganic filler and a binder. By limiting the particle size of the inorganic filler, the size particle grading is achieved, which can make the safety coating have a denser structure, thereby reducing the probability of contact between the positive and negative electrodes, thereby improving the safety performance of the battery cell. At the same time, the amount of binder in the safety coating is optimized to promote the absorption of the electrolyte by the safety coating, which can improve the rate performance, low-temperature discharge performance and cycle performance of the battery cell.

[0105] The third aspect of the present invention provides a method for preparing the above-mentioned electrode sheet, comprising the steps of:

[0106] S100, mixing the first adhesive with water and performing gluing to obtain a glue solution;

[0107] S200, uniformly mixing the first conductive agent and the inorganic filler with the glue, or uniformly mixing the first conductive agent, the thermally stable active substance and the inorganic filler with the glue to obtain a safety coating slurry;

[0108] S300, coating the aqueous safety coating slurry onto one or both sides of the current collector, or onto the surface of the active material layer away from the current collector, to obtain the electrode sheet.

[0109] The method for preparing an electrode sheet according to an embodiment of the present invention has at least the following beneficial effects: by introducing a safety coating into the electrode sheet and limiting the particle size of the inorganic filler and the content of the binder in the safety coating, the present invention can improve the rate performance, low-temperature discharge performance and cycle performance of the battery cell while improving the safety performance of the battery cell without changing the original process. This method is not only simple in process, but also has non-harsh reaction conditions, is compatible with the original preparation process, and has the potential for large-scale application.

[0110] In some embodiments of the present invention, the method for preparing the electrode sheet comprises at least one of the following:

[0111] C1) The mass ratio of the first conductive agent, the first binder, and the inorganic filler is (0.5-5): (1-21.2): (73.8-98.5);

[0112] C2) the solid content of the glue is 10% to 30%;

[0113] C3) The viscosity of the glue is 1×10 3 ~3×10 4 mPa·s;

[0114] C4) The solid content of the safety coating slurry is ≥ 10%;

[0115] C5) the viscosity of the safety coating slurry is ≥50 mPa·s;

[0116] C6) the dyne value of the current collector is ≥30 dyn / cm;

[0117] C7) applying the safety coating slurry to one or both sides of the current collector, or the surface of the active material layer away from the current collector, by gravure printing;

[0118] C8) When C7) is included, the oven temperature during gravure printing is 90-110°C and the printing speed is 10-50 m / min;

[0119] C9) The mass ratio of the first conductive agent, the first binder, the inorganic filler, and the thermally stable active substance is (0.5~5): (1~21.2): (1~97.5): (1~97.5).

[0120] In some embodiments of the present invention, the mass ratio of the first conductive agent, the first binder, and the inorganic filler is (0.5-5): (1-21.2): (73.8-98.5). For example, in terms of weight, the first conductive agent can be 0.5-5 parts, the binder can be 1-21.2 parts, and the inorganic filler can be 73.8-98.5 parts.

[0121] In some embodiments of the present invention, the solid content of the glue solution is 10% to 30%, for example, 10% to 20%, 20% to 25%, or 25% to 30%.

[0122] In some embodiments of the present invention, the viscosity of the glue is 1×10 3 ~3×10 4 mPa·s, preferably 1.5×10 4 ~2.5×10 4 mPa·s, more preferably 1.6×10 4 ~2.2×10 4 mPa·s, for example, can be 2×10 4 mPa·s.

[0123] If the solid content and viscosity of the adhesive liquid are too low, it will not only reduce the processing efficiency, but may also cause insufficient adhesion of the water-based safety coating; if the solid content and viscosity are too high, it may make the processing of the water-based safety coating difficult.

[0124] In some embodiments of the present invention, the raw materials of the safety coating further include a heat-stable active substance, and the mass ratio thereof satisfies: first conductive agent: first binder: inorganic filler: heat-stable active substance = (0.5-5): (1-21.2): (1-97.5): (1-97.5). For example, in terms of weight, the first conductive agent may be 0.5-5 parts, the binder may be 1-21.2 parts, the inorganic filler may be 1-97.5 parts, and the heat-stable active substance may be 1-97.5 parts.

[0125] In some embodiments of the present invention, the solid content of the safety coating slurry is ≥10%, preferably 10% to 21%.

[0126] In some embodiments of the present invention, the viscosity of the safety coating slurry is ≥50 mPa·s.

[0127] The solid content of the safety coating slurry should not be less than 10%, and the viscosity should not be less than 50 mPa·s. Too low solid content will not only reduce the production efficiency, but also make it difficult to obtain a water-based safety coating with a specified thickness and surface density, while too low viscosity will be detrimental to the gravure printing process.

[0128] In some embodiments of the present invention, the dyne value of the current collector is ≥30 dyn / cm, preferably ≥38 dyn / cm. When the dyne value of the current collector is lower than 30 dyn / cm, on the one hand, it is not conducive to the wetting of the current collector by the safety coating slurry, resulting in leakage of the primer, and on the other hand, it will reduce the bonding force between the safety coating and the current collector, causing the safety coating to easily fall off during subsequent use, which has an adverse effect on the safety of the battery cell. The dyne value of the current collector is not less than 38 dyn / cm, which can ensure that the primer has a good appearance and morphology, and the safety coating and the current collector have good bonding.

[0129] In some embodiments of the present invention, the safety coating slurry is coated on one or both sides of the current collector, or on the surface of the active material layer away from the current collector, by gravure printing.

[0130] In some embodiments of the present invention, the temperature of the oven during gravure printing is 90-110° C.; the printing speed is not less than 10 m / min, preferably 10-50 m / min.

[0131] When gravure printing is performed, the oven temperature should be 90~110℃ and the printing speed should be 10~50 m / min. If the oven temperature is lower than 90℃, the production efficiency will be reduced. If it is higher than 110℃, there may be problems such as cracking and migration of the conductive agent to the surface. If the printing speed is too low, the production efficiency will also be reduced. If it is too high, the safety coating will be missed, which will have a negative impact on the safety performance of the battery cell.

[0132] In a specific embodiment of the present invention, a method for preparing the above-mentioned electrode sheet is provided, comprising the following steps:

[0133] (1) Using deionized water as a solvent, the first binder, the first conductive agent, and the inorganic filler are uniformly mixed to obtain a safety coating slurry;

[0134] (2) The safety coating slurry obtained in step (1) is transferred to one or both sides of the current collector, or to the surface of the active material layer away from the current collector, by gravure printing, to obtain an electrode sheet in which the safety coating area and the non-safety coating area are alternately arranged along the unwinding direction of the electrode sheet.

[0135] In some embodiments of the present invention, the total length of the electrode sheet containing the safety coating is L, and the length of the safety coating area is L 1 , the length of the non-safety coating area is L 2 , and L 1 >L 2 , L 1 +L 2 =L.

[0136] In some embodiments of the present invention, the safety coating may be applied on both sides (side A and side B) of the electrode sheet, wherein the length of the safety coating area on side A is L A1 , the length of the non-safety coating area is L A2 , and L A1 >L A2 , L A1 +L A2 =L A ; The length of the coating area on the B surface is L B1 , the length of the non-safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B .

[0137] In some preferred embodiments of the present invention, in order to improve production efficiency and reduce costs, LA 2 and LB 2 All are set to 0, that is, L A1 =L B1 =LA =L B .

[0138] In some embodiments of the present invention, when applying the safety coating, it is also necessary to reserve N in the safety coating area or the non-safety coating area along the unwinding direction of the electrode sheet. 1 Slots for tab welding, N 1 ≥0.

[0139] In some embodiments of the present invention, when applying the safety coating, it is also necessary to reserve N in the safety coating area or non-safety coating area perpendicular to the electrode sheet unwinding direction. 2 Slots for tab welding, N 2 ≥0.

[0140] In some embodiments of the present invention, when applying the safety coating, N can also be applied simultaneously along the unwinding direction of the electrode sheet. 3 Safety coating, N 3 ≥1.

[0141] In some embodiments of the present invention, if both sides of the electrode sheet are coated with a safety coating, the A / B side slots must be kept relative when reserving slots for electrode tab welding, and the horizontal and vertical misalignment distances ∆W must not exceed 2 mm.

[0142] In some embodiments of the present invention, if both sides of the electrode sheet are coated with a safety coating, the distance between the left edge of the water-safe surface A and the left edge of the current collector is W along the direction perpendicular to the unwinding direction of the current collector. A1 (That is, the left side of A is blank as W A1 ), the blank on the right side of A is W A2 , the left side of B is blank for W B1 , the blank on the right side of B is W B2 , satisfying 2mm≤W A1 , W A2 ,W B1 , W B2 ≤30mm, and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm.

[0143] In some embodiments of the present invention, the electrode sheet is a positive electrode sheet, and the method for preparing the positive electrode sheet comprises the steps of:

[0144] (10) Using deionized water as a solvent, adding a binder to form a glue solution with a suitable viscosity and solid content, then adding a first conductive agent and an inorganic filler to the glue solution and mixing them evenly, or mixing the first conductive agent, a thermally stable active substance and an inorganic filler with the glue solution evenly to obtain a water-based safety coating slurry;

[0145] (20) The safety coating slurry obtained in step (10) is transferred to one or both sides of the current collector by gravure printing to obtain a positive electrode sheet in which the safety coating area and the non-safety coating area are alternately arranged along the unwinding direction of the current collector.

[0146] Among them, the non-safety coating area corresponds to the head and / or tail of the positive electrode sheet of the battery cell, usually one side of which is an active material and the other side is a blank foil, or a separately set ceramic layer. The ceramic layer usually contains only inorganic fillers and binders, which can reduce the generation of positive current collector burrs in the non-safety coating area during battery cell testing, reduce the probability of contact between the positive current collector and the negative active material, and thus improve the safety performance of the battery cell. However, the ceramic layer needs to be coated in an additional process after the safety coating is set, which not only reduces production efficiency, but also increases production costs.

[0147] In some embodiments of the present invention, the total length of the positive electrode sheet containing the safety coating is L, and the length of the safety coating area is L 1 , the length of the non-aqueous safety coating area is L 2 , and L 1 >L 2 , L 1 +L 2 =L.

[0148] In some embodiments of the present invention, a safety coating may be applied to both sides (side A and side B) of the positive electrode sheet, wherein the length of the safety coating area on side A is L A1 , the length of the non-safety coating area is L A2 , and L A1 >L A2 , L A1 +L A2 =L A ; The length of the safety coating area on the B side is L B1 , the length of the non-safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B .

[0149] In some preferred embodiments of the present invention, in order to improve production efficiency and reduce costs, the function of the ceramic layer can be assumed by the safety coating, that is, the non-safety coating area is also provided with a safety coating. A2 and L B2 are all set to 0, that is, L A1 =L B1 =L A =L B .

[0150] Figure 2 The figure shows a cross-sectional view of a current collector coated with a safety coating along the unwinding direction in one of the specific embodiments of the present invention. In the figure, 02-positive electrode sheet; 021-reserved slot; 022-current collector; 023-safety coating area; 024-non-safety coating area. The safety coating area and non-safety coating area on the A side and B side of the positive electrode sheet can be arranged opposite to each other, as shown in Figure (a); one side can also be arranged with a non-safety coating area and the other side with a safety coating area, as shown in Figure (b). The total length of the current collector with a safety coating is L, and the length of the safety coating area on the B side is L. B1 , the length of the non-safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B =L A1 =L A =L; the non-safety coating area can also be provided with a safety coating, L A2 and L B2 are all set to 0, that is, L A1 =L B1 =L A =L B , as shown in Figure (c).

[0151] In some embodiments of the present invention, when applying the safety coating, it is also necessary to reserve Z slots for electrode tab welding in the safety coating area or non-safety coating area along the unwinding direction of the current collector, where Z≥0.

[0152] In some embodiments of the present invention, when applying the safety coating, it is also necessary to reserve X slots for electrode tab welding in the safety coating area or non-safety coating area perpendicular to the unwinding direction of the current collector, where X≥0.

[0153] In some embodiments of the present invention, when applying the safety coating, Y strips of the safety coating may be simultaneously applied along the unwinding direction of the current collector, where Y≥1.

[0154] When the safety coating is applied, the slot for the electrode tab welding may be reserved or not reserved as required, such as Figure 3 shown.

[0155] In some embodiments of the present invention, if both sides of the current collector are coated with a safety coating, the slots on the A / B sides must be kept relative to each other when reserving slots for electrode tab welding, and the lateral and longitudinal misalignments ∆W must not exceed 2 mm.

[0156] In some embodiments of the present invention, the safety coating is coated on both sides of the current collector, and the distance W between the left edge of the safety coating on the A side of the current collector and the left edge of the current collector is perpendicular to the unwinding direction of the current collector. A1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is A2 The range is 2mm~30mm; the distance W between the left edge of the safety coating on the B side of the current collector and the left edge of the current collector B1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is B2 The range is 2mm~30mm; and W B1 -W A1 ≥1mm, W B2 -W A2 That is to say, if both sides of the current collector are coated with a safety coating, the distance between the left edge of the safety coating on side A and the left edge of the current collector perpendicular to the unwinding direction of the current collector is W. A1 (That is, the left side of A is blank as W A1 ), the blank on the right side of A is W A2 , the left side of B is blank for W B1 , the blank on the right side of B is W B2 , satisfying 2mm≤W A1 , W A2 ≤30mm, 3mm≤W B1 , W B2 ≤30mm, and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm. Figure 4 The figure shows a cross-sectional view of the safety coating perpendicular to the unwinding direction in a specific embodiment of the present invention. In the figure, 021 is a reserved slot; 022 is a current collector; 023 is a safety coating area. This arrangement enables the width of the safety coating on side A to be more than 2 mm wider than that on side B, thereby reducing the bulging of the edge of the primer when it is rolled up.

[0157] In a fourth aspect of the present invention, a lithium-ion battery is proposed, comprising a positive electrode sheet, a negative electrode sheet, and a separator separated between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and / or the negative electrode sheet is the electrode sheet as described above or the electrode sheet obtained by the preparation method as described above.

[0158] Since the lithium-ion battery adopts all the technical solutions of the electrode sheet of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment. That is, the lithium-ion battery introduces a safety coating into the electrode sheet and limits the particle size of the inorganic filler in the safety coating to achieve large and small particle grading, which can make the safety coating have a denser structure and reduce the probability of contact between the positive and negative electrodes, thereby improving the safety performance of the battery cell. At the same time, the amount of binder in the safety coating is optimized to promote the absorption of the electrolyte by the safety coating, thereby improving the rate performance, low-temperature discharge performance and cycle performance of the battery cell.

[0159] In some embodiments of the present invention, the positive electrode sheet is an electrode sheet as described above. The positive electrode sheet includes the positive electrode current collector containing the safety coating and a positive electrode active material layer coated on at least one surface of the positive electrode current collector. The positive electrode current collector is a common positive electrode current collector in the art, such as aluminum foil, but not limited thereto. The positive electrode active material layer includes a positive electrode active material, which is a common positive electrode active material currently used in lithium-ion batteries, including but not limited to a chemical formula such as Li x Ni h Co y M z O 2-d N d (wherein 0.95≤x≤1.2, h>0, y≥0, z≥0, and h+y+z=1, 0≤d≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO 2 、LiNiO 2 、LiVO 2 、LiCrO 2 、LiMn 2 O 4 、LiCoMnO 4 , Li 2 NiMn 3 O 8 、LiNi 0.5 Mn 1.5 O 4 、LiCoPO 4 、LiMnPO 4 、LiFePO 4 、LiNiPO 4 、LiCoFSO 4 , CuS 2 , FeS 2 、MoS 2 、NiS、TiS 2The positive electrode active material may also be subjected to a modification treatment. The method for modifying the positive electrode active material should be known to those skilled in the art. For example, the positive electrode active material may be modified by coating, doping, etc. The material used for the modification treatment may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc.

[0160] In some embodiments of the present invention, the negative electrode sheet is an electrode sheet as described above. The negative electrode sheet includes the negative electrode current collector containing the safety coating and the negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode current collector has no special requirements and can be a copper foil commonly used in the industry. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon-based material, which can be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites, and silicon alloys, or a mixture of silicon negative electrode materials and other commonly used negative electrode active materials. The other negative electrode active materials include but are not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys.

[0161] In some embodiments of the present invention, the diaphragm may be any material suitable for lithium-ion battery diaphragms in the art, for example, it may be a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber, etc. In actual production, the material and structure of the diaphragm are not strictly limited, for example, it may be a multi-layer structure formed by stacking the above materials, it may be a single-layer structure formed by mixing the above materials, or it may be a single-layer structure formed by a single material; as long as it can play the basic role of a diaphragm.

[0162] In some embodiments of the present invention, the lithium battery further comprises an electrolyte, wherein the electrolyte infiltrates the positive electrode, the negative electrode and the separator. The electrolyte comprises an organic solvent, an electrolyte lithium salt and an additive. The electrolyte lithium salt may be LiPF used in a high temperature electrolyte. 6 and / or LiBOB; it can also be LiBF used in low temperature electrolytes 4 、LiBOB、LiPF 6 It can also be LiBF used in the overcharge-proof electrolyte 4 、LiBOB、LiPF 6, LiTFSI; or LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 At least one of the above. The organic solvent may be a cyclic carbonate, including PC, EC; a chain carbonate, including DEC, DMC or EMC; or a carboxylic acid ester, including PP, MA, EA, EP, etc. The additives include but are not limited to film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, and additives for controlling H in the electrolyte. 2 At least one of an additive for increasing the content of O and HF, an additive for improving low temperature performance, and an additive for water-based safety.

[0163] The present invention also proposes a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and / or the negative electrode sheet is the electrode sheet as described above or the electrode sheet obtained by the preparation method as described above. The electrode sheet proposed by the present invention can be applied not only to the above-mentioned lithium-ion battery, but also to other secondary batteries, including sodium-ion batteries, potassium-ion batteries, etc., without any limitation here.

[0164] A fifth aspect of the present invention provides an application of the above-mentioned lithium-ion battery in an energy storage device, an electrical device or an electronic device. BRIEF DESCRIPTION OF THE DRAWINGS

[0165] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0166] Figure 1 A schematic diagram of the structure of a positive electrode sheet including a safety coating provided by the present invention, wherein 01-positive electrode sheet; 011-active material layer; 022-current collector; 023-safety coating;

[0167] Figure 2 A schematic diagram of the cross-sectional structure of a current collector containing a safety coating provided by the present invention along the unwinding direction, wherein 02-positive current collector containing a safety coating; 021-reserved slot; 022-current collector; 023-safety coating; 024-non-safety coating area;

[0168] Figure 3 A top view of a current collector (not striped) including a safety coating provided by the present invention;

[0169] Figure 4A schematic diagram of the cross-sectional structure of a current collector including a safety coating provided by the present invention along the unwinding direction, wherein 021 - reserved slot; 022 - current collector; 023 - safety coating. DETAILED DESCRIPTION

[0170] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0171] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0172] In the description of the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. Unless otherwise specified, each reaction or operation step may be performed in sequence or not. Preferably, the reaction method of the present invention is performed in sequence.

[0173] If no specific techniques or conditions are specified in the following examples, the techniques or conditions described in the literature in the art or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased commercially.

[0174] Example 1

[0175] This embodiment provides a lithium-ion battery, wherein the positive electrode sheet thereof comprises a safety coating, wherein the safety coating comprises a first binder, a first conductive agent Super P Li and an inorganic filler boehmite;

[0176] Wherein, the structural formula of the first binder is:

[0177]

[0178] (1) Preparation of the first binder:

[0179] a) adding 1000 parts by weight of distilled water into a reaction vessel, starting stirring, introducing high-purity nitrogen to deoxygenate for 1 hour, then adding 50 parts by weight of acrylonitrile, 35 parts by weight of lithium acrylate, and 15 parts by weight of methyl acrylate, and heating to 65° C. and maintaining the temperature under an inert atmosphere;

[0180] b) then adding 5 parts by weight of a 20% ammonium persulfate solution as an initiator to initiate the reaction, and reacting for 5 hours;

[0181] c) After the reaction is completed, the mixture is filtered, dried, crushed and sieved to obtain a binder. The proportion of -CN in the binder is n 1 50%, -COOLi accounts for n 2 35%, -COOCH 3 Proportion 3 is 15%, weight average molecular weight M w 3.6×10 5 , number average molecular weight M w 2.0×10 5 , M w / M n =1.8, electrolyte absorption rate c=22.7%.

[0182] (2) Preparation of positive electrode current collector including safety coating:

[0183] Deionized water was used as solvent, and 10 parts of the above-mentioned adhesive was added for gluing. The amount of deionized water was adjusted until a solid content of 15% and a viscosity of 2.2×10 4 mPa·s glue; then 88 parts of inorganic filler boehmite (D v10 , D v50 , D v90 They are 0.2μm, 0.4μm, 0.9μm, C u =4.5, C c =0.89, specific surface area is 9.5m 2 / g) and 2 parts of the first conductive agent SuperP Li were mixed evenly to obtain a safety coating slurry with a solid content of 20% and a viscosity of 750 mPa·s. The safety coating slurry was coated on both sides of the aluminum foil by gravure printing. A2 and L B2 are all set to 0, that is, L A1 =L B1 =L A =L B =L, Z=Y=1, X=4. In addition, the oven temperature during printing needs to be set to 95°C and the printing speed is 30 m / min. Finally, the positive electrode current collector with double-sided primer safety coating is obtained. The double-sided coating surface density of the safety coating is 10.3 mg / 1540.25 mm2 The double-sided thickness is 5.3 μm, the double-sided film resistance is 3.1Ω @0.4T, and the adhesion between the safety coating and the current collector is 1356 N / m.

[0184] (3) Preparation of positive electrode sheet:

[0185] The positive electrode active material, conductive agent (a mixture of conductive carbon black and carbon nanotubes, mass ratio 6:5), PVDF binder and NMP are mixed evenly at a mass ratio of 97.6:1.1:1.3:35 to prepare a positive electrode slurry with a solid content of 75% and a viscosity of 7000 mPa·s. The positive electrode slurry is coated on one side of the above-mentioned current collector aluminum foil containing the safety coating, and after drying and rolling at 85°C, the positive electrode slurry is coated and dried on the other side of the current collector aluminum foil containing the safety coating according to the above method, and then the positive electrode sheet coated with the positive electrode active material layer on both sides is cold pressed; then the edges are trimmed and stripped to prepare a lithium-ion battery positive electrode sheet (film resistance is 0.8Ω@0.4t).

[0186] (4) Preparation of negative electrode sheet:

[0187] Using water as solvent, graphite, thickener and SBR binder were mixed uniformly in a mass ratio of 97.7:1.1:1.2 to prepare a lithium ion battery negative electrode slurry with a solid content of 50% and a viscosity of 5000 mPa·s, which was coated on one side of the current collector copper foil and dried and rolled at 80°C. Then, the negative electrode slurry was coated and dried on the other side of the copper foil according to the above method to obtain a negative electrode sheet coated with active materials on both sides.

[0188] (5) Preparation of electrolyte:

[0189] Lithium hexafluorophosphate (LiPF 6 ) was dissolved in a mixed solvent of dimethyl carbonate (DMC), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (the mass ratio of DMC, EC and EMC was 3:5:2) to obtain an electrolyte.

[0190] (6) Preparation of batteries:

[0191] The prepared positive electrode sheet, negative electrode sheet and separator are wound into a battery cell with a capacity of about 5 Ah. The separator is located between the adjacent positive electrode sheet and negative electrode sheet, the positive electrode is spot welded out with an aluminum tab, and the negative electrode is spot welded out with a nickel tab; the battery cell is then placed in an aluminum-plastic packaging bag, baked, and injected with the above electrolyte, and finally made into a lithium-ion battery through packaging, formation, capacity division and other processes.

[0192] Example 2

[0193] The difference from Example 1 is that the inorganic filler boehmite is 96.94 parts (Dv10 , D v50 , D v90 They are 0.2μm, 0.4μm, 0.9μm, C u =4.5, C c =0.89), the number of the first binder is 1.06 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=0.2), the number of portions of the first conductive agent Super P Li is 2 portions.

[0194] The rest is the same as Example 1 and will not be described again here.

[0195] Example 3

[0196] The difference from Example 1 is that the inorganic filler boehmite is 87.39 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.4μm, 0.9μm, C u =4.5, C c =0.89), the number of the first binder is 10.61 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=2), the number of portions of the first conductive agent Super P Li is 2 portions.

[0197] The rest is the same as Example 1 and will not be described again here.

[0198] Example 4

[0199] The difference from Example 1 is that the inorganic filler boehmite is 76.79 parts (D v10 , D v50 , D v90 They are 0.1μm, 0.4μm, 1.8μm, C u =18, C c =0.89), the number of the first binder is 21.21 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=2), the number of portions of the first conductive agent Super P Li is 2 portions.

[0200] The rest is the same as Example 1 and will not be described again here.

[0201] Example 5

[0202] The difference from Example 1 is that the inorganic filler boehmite is 77.95 parts (D v10 , D v50 , D v90 They are 0.1μm, 0.4μm, 1.8μm, C u =18, C c =0.89), the number of the first binder is 20.05 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0203] The rest is the same as Example 1 and will not be described again here.

[0204] Example 6

[0205] The difference from Example 1 is that the inorganic filler boehmite is 84.64 parts (D v10 , D v50 , D v90 They are 0.15μm, 0.4μm, 1.2μm, C u =8, C c =0.89), the number of the first binder is 13.36 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0206] The rest is the same as Example 1 and will not be described again here.

[0207] Example 7

[0208] The difference from Example 1 is that the inorganic filler boehmite is 91.32 parts (D v10 , D v50 , D v90 They are 0.3μm, 0.4μm, 0.6μm, C u =2, C c =0.89), the number of the first binder is 6.68 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0209] The rest is the same as Example 1 and will not be described again here.

[0210] Example 8

[0211] The difference from Example 1 is that the inorganic filler boehmite is 84.64 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.3μm, 0.9μm, C u =4.5, C c =0.5), the number of the first binder is 13.36 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0212] The rest is the same as Example 1 and will not be described again here.

[0213] Example 9

[0214] The difference from Example 1 is that the inorganic filler boehmite is 91.32 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.6μm, 0.9μm, C u =4.5, C c =2), the number of the first binder is 6.68 parts (the mass fraction of the first binder in the safety coating satisfies w= w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0215] The rest is the same as Example 1 and will not be described again here.

[0216] Example 10

[0217] The difference from Example 1 is that the inorganic filler boehmite is 92.58 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.74μm, 0.9μm, C u =4.5, C c =3.04), the number of the first binder is 5.42 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0218] The rest is the same as Example 1 and will not be described again here.

[0219] Embodiment 11

[0220] The difference from Example 1 is that the inorganic filler boehmite is 77.95 parts (D v10 , D v50 , D v90 They are 0.1μm, 0.2μm, 0.45μm, C u =4.5, C c =0.89), the number of the first binder is 20.05 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0221] The rest is the same as Example 1 and will not be described again here.

[0222] Example 12

[0223] The difference from Example 1 is that the inorganic filler boehmite is 97 parts (D v10 , D v50 , D v90 2μm, 4μm, 9μm, respectively, C u =4.5, C c =0.89), the number of the first binder is 1 (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0224] The rest is the same as Example 1 and will not be described again here.

[0225] Embodiment 13

[0226] The difference from Example 1 is that the first binder is replaced by PVDF binder, and the solvent is replaced by NMP (N-methylpyrrolidone) from deionized water.

[0227] The rest is the same as Example 1 and will not be described again here.

[0228] Embodiment 14

[0229] The difference from Example 1 is that during coating, a ceramic layer is separately provided in the non-aqueous safety coating area of ​​the B surface, i.e., L B2 ≠0, such as Figure 3As shown, the total length of the current collector containing the water-based safety coating is L, and the length of the water-based safety coating area on the B surface is L B1 , the length of the non-aqueous safety coating area is L B2 , and L B1 >L B2 , L B1 +L B2 =L B =L A1 =L A =L.

[0230] The rest is the same as Example 1 and will not be described again here.

[0231] Comparative Example 1

[0232] The difference from Example 1 is that the inorganic filler boehmite is 72.94 parts (D v10 , D v50 , D v90 They are 0.08μm, 0.4μm, 2.25μm, C u =28.1, C c =0.89), the number of the first binder is 25.06 parts (the mass fraction of the first binder in the safety coating satisfies w= w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0233] The rest is the same as Example 1 and will not be described again here.

[0234] Comparative Example 2

[0235] The difference from Example 1 is that the inorganic filler boehmite is 92.24 parts (D v10 , D v50 , D v90 They are 0.35μm, 0.4μm, 0.52μm, C u =1.5, C c =0.88), the number of the first binder is 5.76 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0236] The rest is the same as Example 1 and will not be described again here.

[0237] Comparative Example 3

[0238] The difference from Example 1 is that the inorganic filler boehmite is 83.15 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.27μm, 0.9μm, C u =4.5, C c =0.41), the number of the first binder is 14.85 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0239] The rest is the same as Example 1 and will not be described again here.

[0240] Comparative Example 4

[0241] The difference from Example 1 is that the inorganic filler boehmite is 93 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.8μm, 0.9μm, C u =4.5, C c =3.56), the number of the first binder is 5 (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0242] The rest is the same as Example 1 and will not be described again here.

[0243] Comparative Example 5

[0244] The difference from Example 1 is that the inorganic filler boehmite is 85.47 parts (D v10 , D v50 , D v90 They are 0.08μm, 0.8μm, 2.25μm, C u =28.1, C c =3.56), the number of the first binder is 12.53 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=1.89), the number of portions of the first conductive agent Super P Li is 2 portions.

[0245] The rest is the same as Example 1 and will not be described again here.

[0246] Comparative Example 6

[0247] The difference from Example 1 is that the inorganic filler boehmite is 97.47 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.4μm, 0.9μm, C u =4.5, C c =0.89), the first binder is 0.53 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=0.1), the number of portions of the first conductive agent Super P Li is 2 portions.

[0248] The rest is the same as Example 1 and will not be described again here.

[0249] Comparative Example 7

[0250] The difference from Example 1 is that the inorganic filler boehmite is 74.14 parts (D v10 , D v50 , D v90 They are 0.2μm, 0.4μm, 0.9μm, C u =4.5, C c =0.89), the number of the first binder is 23.86 parts (the mass fraction of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , k=4.5), the number of portions of the first conductive agent Super P Li is 2 portions.

[0251] The rest is the same as Example 1 and will not be described again here.

[0252] Comparative Example 8

[0253] The difference from Example 1 is that the surface of the positive electrode current collector is not coated with a safety coating.

[0254] The rest is the same as Example 1 and will not be described again here.

[0255] Test Case

[0256] In order to verify the effect of the introduction of the safety coating of the present invention on the performance of the battery cell, the particle size of the inorganic filler, the electrolyte absorption rate c of the binder and the double-sided film resistance of the safety coating, as well as the puncture performance, low-temperature discharge performance, rate performance and cycle performance of the battery cell were tested.

[0257] Particle size test method: The inorganic filler was dispersed with water as a dispersant, and the particle size of the inorganic filler was tested using a laser particle size analyzer (Malvern, Mastersizer 3000).

[0258] Electrolyte absorption rate c test method: Pour the binder solution into a polytetrafluoroethylene plate, bake it to volatilize the deionized water and obtain an adhesive polymer film. The thickness of the film is controlled at 100μm, and it is cut into a 50mm long × 50mm wide film. After that, the film is vacuum dried for 24 hours and weighed. Then, the completely dried film is immersed in an electrolyte at 80℃ for 12 hours and then taken out. After wiping off the electrolyte attached to the surface of the film, the weight of the film after absorbing the electrolyte is weighed. The increase rate (%) of the weight of the film before and after immersion in the electrolyte is the 80℃ absorption rate of the binder. o C of electrolyte absorption rate.

[0259] Diaphragm resistance test method: The instrument used for the diaphragm resistance test is the ACCFILM diaphragm resistance test system (model TT-ACCF-G2A) of Hangzhou Chuanyuan Technology Co., Ltd. The pressure during the test is 0.4 t and the pressure holding time is 10 s.

[0260] Needle penetration test method: charge to 4.45 V at 1.0 C constant current and constant voltage at room temperature, with a cut-off rate of 0.05 C, and then subject the fully charged cell to a needle penetration test. During the test, the deep pit side of the cell faces upward, and a steel nail with a diameter of 4.0 mm is used to completely pierce the cell at a speed of 40 mm / s. The nail penetration position is located at the left, middle, and right positions of the largest surface of the cell (5 cells are tested at each position). Keep for 1 hour. The cell passes the test if it does not catch fire or explode.

[0261] Low temperature discharge performance test method: discharge at 1 C constant current to 3 V, leave for 5 min; set the temperature box to 25 ° C and leave for 60 min; charge at 1.0 C constant current and constant voltage to 4.45 V, with a cut-off rate of 0.02 C; leave for 5 min, discharge at 0.2 C constant current to 3 V, and record the capacity when discharged to 3 V at 0.2 C as the initial capacity C 0 ; Set the incubator to 25℃ and leave for 60 min; Charge to 4.45 V at 1.0 C constant current and constant voltage, with a cutoff rate of 0.02 C; Leave for 5 min, set the incubator to -10℃, leave for 120 min, then discharge the cell at 0.2 C to 3.0 V, and record the capacity C when discharged to 3.4 V and 3.0 V 1 and C 2 , C 1 With C 0 The ratio is the capacity retention rate when discharged to 3.4 V at -10°C.

[0262] The rate discharge performance test method is as follows: discharge at 1 C constant current to 3 V and leave for 5 min; charge at 1.0 C constant current and constant voltage to 4.45 V, with a cut-off rate of 0.02 C and leave for 5 min; discharge at 0.2 C constant current to 3 V, and record the capacity when discharged to 3 V at 0.2 C as the initial capacity C 3 ; Charge to 4.45 V at 1.0 C constant current and constant voltage, cut-off rate 0.02 C, and leave for 5 min; then discharge the cell at 0.2 C to 3.0 V, and record the capacity C when discharged to 3.4 V and 3.0 V 4 and C 5 , C 4 With C 3 The ratio is the capacity retention rate when discharged to 3.4 V at 2C.

[0263] Cycling performance test method: Under the condition of ambient temperature of 25±2℃, discharge the battery cell at 0.2 constant current to 3.0V, then charge it to 4.45V at 3C constant current and constant voltage, with a cut-off rate of 0.05C, and record the voltage, internal resistance, capacity and thickness of the battery cell when it is fully charged for the first time (600gPPG is used for thickness measurement). The cycling process is in accordance with the following HFC standard: discharge to 3V at 0.2C constant current; charge to 4.25V at 3.0C constant current; charge to 4.25V at 2.5C constant current; charge to 4.45V at 2.0C constant current; charge to 4.50V at 1.4C constant current and constant voltage, with a cut-off rate of 0.3C; charge to 4.45V at 2A constant current and constant voltage, with a cut-off rate of 0.05C; discharge to 3V at 1.0C constant current. The above steps are considered one cycle. After 49 cycles, low current recovery is performed according to the following system: charge to 4.25 V at 3.0 C constant current; charge to 4.25 V at 2.5 C constant current; charge to 4.45 V at 2.0 C constant current; charge to 4.50 V at 1.4 C constant current and constant voltage, with a cut-off rate of 0.3 C; charge to 4.45 V at 2 A constant current and constant voltage, with a cut-off rate of 0.05 C; discharge to 3 V at 0.2 C constant current; charge to 4.45 V at 3.0 C constant current and constant voltage, with a cut-off rate of 0.05 C. Record the fully charged cell voltage, internal resistance, and thickness (600 gPPG is used for thickness measurement) every 100 cycles.

[0264] The parameter settings and test results of Examples 1-14 and Comparative Examples 1-8 are shown in Table 1 below:

[0265] Table 1

[0266]

[0267] From the comparison of the test results in the above table, it can be seen that compared with Comparative Examples 1-8, the particle size D of the inorganic filler in the safety coating in Examples 1-14 isv10 , D v50 , D v90 Satisfy 2≤Cu=D v90 / D v10 ≤18,0.5≤C c =D v50 ×D v50 / (D v10 ×D v90 )≤3.1, the amount of binder w satisfies: w=k×(C u ) 0.5 / D v50 , 0.2≤k≤2, where k is a constant related to the density of the inorganic filler. The safety performance of the corresponding battery cell is significantly improved, and the pass rate of the puncture test is increased from 0% to 100%. At the same time, the low-temperature discharge performance, rate discharge performance and cycle performance are significantly improved.

[0268] In summary, the safety coating provided by the present invention can improve the safety performance of the battery cell while improving the rate performance, low temperature discharge performance and cycle performance of the battery cell by limiting the particle size of the inorganic filler and selecting the binder. v10 , D v50 , D v90 Should satisfy 2≤Cu=D v90 / D v10 ≤18,0.5≤C c =D v50 ×D v50 / (D v10 ×D v90 )≤3.1,C u and C c are the uniformity coefficient and curvature coefficient of the inorganic filler, D v10 , D v50 , D v90 are the particle sizes corresponding to the cumulative values ​​of the volume distribution of the inorganic filler reaching 10%, 50% and 90% respectively. When the particle size of the inorganic filler satisfies the above relationship, the continuity of its gradation curve is good, and the gradation of fine particles and coarse particles is good, which can make the safety coating have a denser structure, thereby reducing the probability of short circuit between the positive and negative electrodes and improving the safety performance of the battery cell. The mass fraction w of the first binder should satisfy w=k×(C u ) 0.5 / D v50, 0.2≤k≤2, when k is in the above range, the binder not only has sufficient bonding force, the polarization of the battery cell is small, but also can promote the absorption of the electrolyte by the safety coating, and improve the rate performance, low-temperature discharge performance and cycle performance of the battery cell. Finally, the safety coating provided by the present invention, by limiting the particle size of the inorganic filler, realizes the grading of large and small particles, can make the safety coating have a denser structure, thereby reducing the probability of contact between the positive and negative electrodes, thereby improving the safety performance of the battery cell. At the same time, the amount of binder in the safety coating is optimized to promote the absorption of the electrolyte by the safety coating, which can improve the rate performance, low-temperature discharge performance and cycle performance of the battery cell. The battery cell provided by the present invention, when satisfying the above relationship, can achieve a puncture pass rate of 100%, and at the same time, the capacity retention rate after 800 cycles at 25°C is not less than 88%, the discharge capacity at -10°C is not less than 70% @3.4V, and the discharge capacity at 2C is not less than 70% @3.4V.

[0269] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A safety coating for an electrode sheet in a secondary battery, characterized in that: The raw materials of the safety coating include inorganic filler and a first binder; The non-uniformity coefficient C of the inorganic filler u Satisfy 2≤C u ≤18, curvature coefficient C c Satisfy 0.5≤C c ≤3.1; The mass fraction w of the first binder in the safety coating satisfies w=k×(C u ) 0.5 / D v50 , and 0.2≤k≤2, k is a constant, and the mass fraction w of the first binder in the safety coating ranges from 1% to 21.2%; Among them, the non-uniformity coefficient C u The calculation formula is: C u =D v90 / D v10 , the curvature coefficient C c The calculation formula is: C c =D v50 ×D v50 / (D v10 ×D v90 ); D v10 , D v50 , D v90 They are the particle sizes corresponding to the cumulative values ​​of the volume distribution of the inorganic filler reaching 10%, 50% and 90% respectively.

2. The safety coating according to claim 1, characterized in that The median particle size D of the inorganic filler v50 The range is 0.2~4μm, and the specific surface area is 5~50m 2 / g; And / or, the inorganic filler includes one or more of alumina, boehmite, aluminum hydroxide, magnesium hydroxide, silicon dioxide, titanium dioxide, lithium iron phosphate, lithium manganese iron phosphate, lithium aluminum titanium phosphate, lithium lanthanum titanate or lithium lanthanum zirconium oxide; And / or, the mass fraction of the inorganic filler in the safety coating is 73.8% to 98.5%.

3. The safety coating according to claim 1, characterized in that: The first binder includes one or more of polyvinylidene fluoride binder, sodium carboxymethyl cellulose binder or polyacrylate binder.

4. The safety coating according to claim 3, characterized in that The first binder is a polyacrylate binder, and the structural formula of the polyacrylate binder is: ; wherein each occurrence of R1 is independently selected from H, Li or Na; Each occurrence of R2 is independently selected from substituted or unsubstituted C1~C 10 The alkyl group; And 5≤(x+z) / y≤20, 1.2≤z / x≤2, x, y, z are not 0; And / or, the weight average molecular weight M of the polyacrylate binder w The range is 200000~500000, the number average molecular weight M n The range is 100000~400000; And / or, the weight average molecular weight M of the polyacrylate binder w and number average molecular weight M n The ratio M w / M n ≤3; And / or, the electrolyte absorption rate of the polyacrylate binder at 80° C. is 10% to 50%.

5. The safety coating according to any one of claims 1 to 4, characterized in that: The raw material of the safety coating further includes a first conductive agent; the safety coating satisfies at least one of the following: A1) The mass fraction of the first conductive agent in the safety coating is 0.5% to 5%; A2) The mass ratio of the first conductive agent, the first binder, and the inorganic filler is (0.5-5): (1-21.2): (73.8-98.5); A3) The raw materials of the safety coating also include heat-stable active substances; A4) When A3) is included, the mass ratio of the first conductive agent, the first binder, the inorganic filler, and the thermally stable active material is (0.5-5): (1-21.2): (1-97.5): (1-97.5); A5) When A3) is included, the thermally stable active material includes one or both of lithium iron phosphate and lithium manganese iron phosphate.

6. An electrode sheet, characterized in that: include: current collector; active material layer; A safety coating as claimed in any one of claims 1 to 5.

7. The electrode sheet according to claim 6, characterized in that: The safety coating is coated on at least one side of the current collector, and the active material layer is coated on a side of the safety coating away from the current collector and / or on a side of the current collector away from the safety coating; Alternatively, the active material layer is coated on at least one side of the current collector, and the safety coating is coated on a side of the active material layer away from the current collector and / or on a side of the current collector away from the active material layer.

8. The electrode sheet according to claim 7, characterized in that: The safety coating is coated on both sides of the current collector; the safety coating satisfies at least one of the following: B1) the double-sided thickness of the safety coating is 1-20 μm; B2) The double-sided coating density of the safety coating is 2-35 mg / 1540.25 mm 2 ; B3) The double-sided membrane resistance of the safety coating tested under a pressure of 0.4 t is 0.5~5Ω; B4) The double-sided thickness d of the safety coating and the value of the double-sided diaphragm resistance R under a pressure of 0.4 t satisfy the condition: 2≤R×d≤50; B5) The distance W between the left edge of the safety coating on the A side of the current collector and the left edge of the current collector along the direction perpendicular to the unwinding direction of the current collector A1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is A2 The range is 3mm~30mm; the distance W between the left edge of the safety coating on the B side of the current collector and the left edge of the current collector B1 The range is 2mm~30mm, and the distance W between the right edge and the right edge of the current collector is B2 The range is 3mm~30mm; and W B1 -W A1 ≥1mm, W B2 -W A2 ≥1mm.

9. A method for preparing an electrode sheet according to any one of claims 6 to 8, characterized in that: Includes steps: Mixing the first binder with water and performing gluing to obtain a glue solution; The first conductive agent and the inorganic filler are mixed evenly with the glue, or the first conductive agent, the thermally stable active substance and the inorganic filler are mixed evenly with the glue to obtain a safety coating slurry; The safety coating slurry is applied to one or both sides of the current collector, or the surface of the active material layer away from the current collector to obtain the electrode sheet.

10. The method for preparing an electrode sheet according to claim 9, characterized in that: Include at least one of the following: C1) The mass ratio of the first conductive agent, the first binder, and the inorganic filler is (0.5-5): (1-21.2): (73.8-98.5); C2) the solid content of the glue is 10% to 30%; C3) The viscosity of the glue is 1×10 3 ~3×10 4 mPa·s; C4) The solid content of the safety coating slurry is ≥ 10%; C5) the viscosity of the safety coating slurry is ≥50 mPa·s; C6) the dyne value of the current collector is ≥30 dyn / cm; C7) applying the safety coating slurry to one or both sides of the current collector, or the surface of the active material layer away from the current collector, by gravure printing; C8) When C7) is included, the oven temperature during gravure printing is 90-110°C and the printing speed is 10-50 m / min; C9) The mass ratio of the first conductive agent, the first binder, the inorganic filler, and the thermally stable active substance is (0.5~5): (1~21.2): (1~97.5): (1~97.5).

11. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet and / or the negative electrode sheet is the electrode sheet according to any one of claims 6 to 8 or the electrode sheet obtained by the preparation method according to any one of claims 9 to 10.

12. Use of the lithium-ion battery according to claim 11 in an energy storage device, an electrical device or an electronic device.

Citation Information

Patent Citations

  • Battery cell, preparation method thereof and lithium ion battery

    CN118970147A